2012
DOI: 10.6009/jjrt.2012_jsrt_68.6.697
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Rate of Radiation Exposure through Lateral Contact of Patients Undergoing Radionuclide Examination

Abstract: During examinations using radionuclide methods, technicians sometimes need to interact directly with patients. The initial point of contact is when they assist patients onto the examination table, the second is when the patients are positioned for radionuclide examination, and the third occurs if the patients experience a sudden change in condition and assistance is deemed necessary. The dose of radiation increases proportionately to the size of the area being treated. Therefore, we verified that the lateral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Some published studies suggest that staff interacting with the lateral surface from the trunk of the body of a patient undergoing radionuclide examination has a lower radiation dose than the anterior surface because of the smaller area. 1,10) The 18 F-FDG injected activity for humans ranges from 370 to 740 MBq (10-20 mCi) for adults and 3.7 to 5.2 MBq/kg (0.10-0.14 mCi/kg) for children. 35) Although the 18 F-FDG administered activity in veterinary patients is smaller than that in humans, there is closer contact with the radioactive patient due to handling of anesthetized patients and the duration of time close contact is longer than that in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some published studies suggest that staff interacting with the lateral surface from the trunk of the body of a patient undergoing radionuclide examination has a lower radiation dose than the anterior surface because of the smaller area. 1,10) The 18 F-FDG injected activity for humans ranges from 370 to 740 MBq (10-20 mCi) for adults and 3.7 to 5.2 MBq/kg (0.10-0.14 mCi/kg) for children. 35) Although the 18 F-FDG administered activity in veterinary patients is smaller than that in humans, there is closer contact with the radioactive patient due to handling of anesthetized patients and the duration of time close contact is longer than that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dramatic concern about the radiation safety of the medical staff during the utility of PET radiopharmaceutical technology. 1,[5][6][7][8][9][10][11][12][13][14][15] There is no standard 18 F-FDG PET/CT protocol for veterinary hospitals, and there are few studies on staff dose data for PET imaging. 16,17) Martinez et al 16) reported that the whole-body doses per scan in veterinary staff were higher than those of the medical staff because of the need for general anesthesia in animal patients to minimize movement and physically active muscle uptake, making the veterinary staff closer to patients than the medical staff.…”
Section: Introductionmentioning
confidence: 99%